Heat Stroke Induces Pyroptosis in Spermatogonia via the cGAS-STING Signaling Pathway - Deng, Q-F; Liu, Y; Chu, H; Peng, B; Li, X; Cao, Y-S (Physiological research, 2024)
To explore the mechanism whereby cGAS-STING pathway regulates the pyroptosis of cryptorchidism cells, with a view to finding a new strategy for clinically treating cryptorchidism-induced infertility. Spermatogonial GC-1 cells were heat stimulated to simulate the heat hurt microenvironment of cryptorchidism. The cell viability was assayed by CCK-8, and cellular DNA damage was detected by gamma-H2AX immunofluo-rescence assay. Flow cytometry was employed to assess pyroptosis index, while western blot, ELISA and PCR were used to examine the expressions of pyroptosis-related proteins (Caspase-1, IL-1beta, NLRP3) and cGAS-STING pathway proteins (cGAS, STING). After STING silencing by siRNA, the expressions of pyroptosis-related proteins were determined. Pyroptosis occurred after heat stimulation of cells. Morphological detection found cell swelling and karyopyknosis. According to the gamma-H2AX immunofluorescence (IFA) assay, the endonuclear green fluorescence was significantly enhanced, the gamma-H2AX content markedly increased, and the endonuclear DNA was damaged. Flow cytometry revealed a significant increase in pyroptosis index. Western blot and PCR assays showed that the expressions of intracellular pyrogenic proteins like Caspase-1, NLRP3 and GSDMD were elevated. The increased STING protein and gene expressions in cGAS-STING pathway suggested that the pathway was intracellularly activated. Silencing STING protein in cGAS-STING pathway led to significantly inhibited pyroptosis. These results indicate that cGAS-STING pathway plays an important role in heat stress-induced pyroptosis of spermatogonial cells. After heat stimulation of spermatogonial GC-1 cells, pyroptosis was induced and cGAS-STING pathway was activated. This study can further enrich and improve the molecular mechanism of cryptorchidism.
Keywords: spermatogonie; Male; Pyroptosis; Chromogranin A; Heat Stroke; NLR Family, Pyrin Domain-Containing 3 Protein; signální transdukce; Acetates; mužské pohlaví; kaspasa 1; fenoly; Signal Transduction; Spermatogonia; Caspase 1; protein NLRP3; lidé; nukleotidyltransferasy; acetáty; úpal; Humans; pyroptóza; Nucleotidyltransferases; Cryptorchidism; kryptorchismus; Phenols; chromogranin A